Investigations into critical earthquake load models within deterministic and probabilistic frameworks. - Abbas, A.M (Earthquake engineering & structural dynamics.)
This paper deals with the determination of critical earthquake load models for linear structures subjected to single point seismic inputs. The primary objective of this study is to examine the realism in critical excitations and critical responses vis a vis the framework adopted for the study and constraints that these excitations are taken to satisfy. Two alternative approaches are investigated. In the first approach, the critical earthquake is expressed in terms of a Fourier series that is modulated by an enveloping function that imparts transient nature to the inputs. The Fourier coefficients are taken to be deterministic and are constrained to satisfy specified upper and lower bounds. Estimates on these bounds, for a given site, are obtained by analysing past earthquake records from the same site or similar sites. The unknown Fourier coefficients are determined such that the response of a given structure is maximized subjected to these bounds and additional constraints on intensity, peak ground acceleration, peak ground velocity and peak ground displacement. In the second approach, the critical earthquake is modelled as a partially specified non stationary Gaussian random process which is defined in terms of a stationary random process of unknown power spectral density (psd) function modulated by a deterministic envelope function. The input is constrained to possess specified variance and average zero crossing rate. Additionally, a new constraint in terms of entropy rate representing the expected level of disorder in the excitation is also imposed. The unknown psd function of the stationary part of the input is determined so taht the response of a given structure is maximized. The optimization problem in both these approaches is solved by using sequential quadratic programming method. The procedures developed are illustrated by considering the seismic response of a tall chimney and an earth dam. It is concludd that the imposition of lower and upper bounds on Fourier coefficients in the first approach and contraints on amount of disorder in the second approach are crucial in arriving at realistic critical excitations.